1972
DOI: 10.1002/1097-0142(197206)29:6<1518::aid-cncr2820290616>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Malignant giant cell tumor of soft parts. An analysis of 32 cases

Abstract: The malignant giant cell tumor of soft parts is an extraskeletal malignant neoplasm somewhat resembling a giant cell tumor of bone and consisting of multinucleated giant cells (occasionally containing asteroid bodies), monon‐nuclear histiocytes, and fibroblasts arranged in a multinodular pattern. Thirty‐two cases of this tumor in the AFIP files were reviewed and subdivided into a superficial and a deep group; the superficial tumors (12 cases) were small and occurred in the region of the subcutis and superficia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
144
2
1

Year Published

1973
1973
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(150 citation statements)
references
References 3 publications
3
144
2
1
Order By: Relevance
“…Three (cats 1, 2, and 3) were giant cell variants of malignant fibrous histiocytoma as described by Guccion and Enzinger [5] who reviewed 32 such malignant extraskeletal giant cell tumors in man and concluded that they were malignant tumors of histiocytes.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Three (cats 1, 2, and 3) were giant cell variants of malignant fibrous histiocytoma as described by Guccion and Enzinger [5] who reviewed 32 such malignant extraskeletal giant cell tumors in man and concluded that they were malignant tumors of histiocytes.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the histiocytic cells may assume an epithelioid appearance or they may be multinucleated, as in the giant cell tumor of soft tissues, which may contain extremely large giant cells with numerous nuclei [5]. This cellular pleomorphism was responsible for the plethora of names given to this group of tumors, including epithelioid sarcoma, malignant histiocytoma, and reticulum cell sarcoma of soft parts [4, 111. These tumors are malignant, and there are metastases and local recurrences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The five previously described subtypes of MFH seem to have few links, if any, to tumors of fibrohistiocytic differentiation, and the angiomatoid variant is no longer thought to be a fully sarcomatous member of STS (Costa and Weiss, 1990;Fanburg-Smith and Miettinen, 1999). Rather, the giant cell variant shares characteristics common to giant-cell-rich osteosarcoma of soft tissues (Guccion and Enzinger, 1972) and a number of inflammatory MFH overlap with inflammatory LMS (Merchant et al, 1995). Additionally, poorly differentiated myxoid MFH merge with pleomorphic MFH (Weiss and Enzinger, 1977), which are no longer thought to be tumors of true histiocytic differentiation.…”
Section: Derré Et Almentioning
confidence: 99%
“…Soon after the first definition of the tumor by Salm and Sissons in 1972, Guccion and Enzinger have described the malignant type of the tumor in the analysis of another series composed of 32 cases [4]. Later Soule and Enriquez has reported the benign and malignant forms of histiocytic lesions in 65 cases including 5 tumors which were histologically similar to the tumors defined by Guccion and Enzinger [5].…”
Section: Discussionmentioning
confidence: 93%